THE PLACE OF THE MODESTY MAXIM AMONG OTHER POLITENESS MAXIMS (Journal of Multidisciplinary Sciences and Innovations, 2025)
The concept of politeness occupies a central position in pragmatic and sociolinguistic studies, serving as a key mechanism through which social harmony and interpersonal relations are maintained. Among various theoretical models, Geoffrey Leech’s Politeness Principle and its associated maxims have played a significant role in explaining how speakers manage social interaction through language. This article focuses on the modesty maxim, examining its place, function, and interaction with other politeness maxims such as tact, generosity, approbation, agreement, and sympathy. Through theoretical analysis and illustrative examples, the study argues that the modesty maxim functions as a mediating and identity-regulating principle that balances self-presentation and social expectations. The paper further demonstrates that while the modesty maxim is closely interconnected with other maxims, it possesses distinctive pragmatic and cultural significance, particularly in collectivist societies. The analysis contributes to a deeper understanding of politeness as a dynamic and context-dependent phenomenon rather than a fixed set of universal rules.